2012
DOI: 10.1177/030089161209800317
|View full text |Cite
|
Sign up to set email alerts
|

Hope Herth Index (HHI): A Validation Study in Italian Patients with Solid and Hematological Malignancies on Active Cancer Treatment

Abstract: The Italian version of HHI is a valid and reliable assessment tool - useful to initiate conversation with someone who is troubled but finds it difficult to talk - in patients with either solid or hematological malignancies on active cancer treatment during the non-advanced stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 25 publications
4
47
0
3
Order By: Relevance
“…Thus, the identification of the levels of hope of patients may offer benefits for nurses who plan the care, with a view to more appropriate actions to encourage hope and to reduce the impact of the disease on daily life of patients with cancer. In this study, the levels of hope found (median of 36 and 37 points respectively in the first and second moments) were similar to those of studies conducted internationally, such as in Italy, where patients on antineoplastic treatment had a median score of 36.8 points on the same scale (5) and in Poland, where patients with cancer had levels of 37.5 of hope. (6) The dimension with the lowest score on the Herth Hope Index was related to the patients' loneliness, which presented scores of hope inferior to the other domains of the scale.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, the identification of the levels of hope of patients may offer benefits for nurses who plan the care, with a view to more appropriate actions to encourage hope and to reduce the impact of the disease on daily life of patients with cancer. In this study, the levels of hope found (median of 36 and 37 points respectively in the first and second moments) were similar to those of studies conducted internationally, such as in Italy, where patients on antineoplastic treatment had a median score of 36.8 points on the same scale (5) and in Poland, where patients with cancer had levels of 37.5 of hope. (6) The dimension with the lowest score on the Herth Hope Index was related to the patients' loneliness, which presented scores of hope inferior to the other domains of the scale.…”
Section: Discussionsupporting
confidence: 86%
“…(5,6) It is important to stress that these results trigger reflection on the characteristics of the care provided to patients with cancer and the need for implementing care actions that emphasize the interpersonal and subjective aspect of care in order to promote a sense of hope among these patients. Accordingly, nurses, as the professionals closest to patients with cancer during their treatment, must be alert to the wishes and feelings of these individuals, so that the characteristics that drain their hopes can be worked continuously, through active listening, offering detailed information and openness to receive complaints, enabling them to participate consistently in the therapeutic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score ranges from 12 to 48, and the higher the score the higher level of hope [6]. Studies show that, based on patients with various medical conditions, the median was 36 points [12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Eleven papers assessed the psychometric properties of the Herth Hope Index. The 11 studies were conducted in the following locations: 3 (27%) in Norway, 2 (18%) in the United States, 2 (18%) in Brazil, 1 (9%) in Sweden, 1 (9%) in Italy, 1 (9%) in Hong Kong, and 1 (9%) in the Netherlands . Three (27%) studies were conducted in Norwegian, 2 (18%) in English, 2 (18%) in Portuguese, 1 (9%) in Swedish, 1 (9%) in Italian, 1 (9%) in Chinese, and 1 (9%) in Dutch …”
Section: Assessment Of Individual Scalesmentioning
confidence: 99%